Komparasi Hasil Belajar Model Kooperatif Tipe Talking Stick dengan Model Pembelajaran Expositori - Fauzan Fajri; Andy Riski Pratama (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study is motivated by the fact that most mathematics learning activities are boring and uninteresting. Maths is only taught with the lecture method and practice questions. This type of research is a pre-experiment with The Static Group Comparison Design research design. The population in this study were all VII grade students of MTsS TI Candung in the 2023/2024 academic year. Sampling was carried out randomly by first testing the normality, homogeneity and equality of means on population data. The samples in this study were VIII.2 class students as the experimental class and VIII.3 class students as the control class. Learning outcome data were obtained from test questions. Based on the analysis of the test results of understanding of mathematical concepts using t-test, obtained and , because it means H0 is rejected and H1 is accepted. While using Minitab obtained Pvalueyang means at the real level, Thus it can be concluded that the Comparative Mathematics learning outcomes of students using the Talking Stick Type Cooperative learning model, better than the mathematics learning outcomes of students through the expository learning model in class VII MTsS TI Candung Lesson Year 2023/2024.